Phonemic correspondence in Deli Malay and Javanese: a comparative historical linguistic study - Indra Purnawan Panjaitan; Dwi Widayati; Dardanila (JL3T (Journal of Linguistics, Literature and Language Teaching), 2026)
This study investigates the phonemic correspondences between Deli Malay and Javanese, two Austronesian languages that have undergone intense contact in eastern Sumatra due to historical migration and interethnic interaction. Using a comparative historical linguistic approach, the research aims to identify systematic sound changes and trace linguistic relationships between the two languages. The data were derived from 200 Swadesh vocabulary items collected through written sources and oral validation from native speakers. From this corpus, 24 cognate pairs were found to exhibit phonemic correspondences. The analysis focuses on consonantal and vowel shifts, highlighting regular patterns such as /b/ ~ /w/, /a/ ~ /o/, and /d/ or /t/ ~ /l/, as well as processes like lenition, assimilation, centralization, and diphthong simplification. These regularities suggest not only potential common ancestry but also phonological convergence due to prolonged contact. Some irregular shifts indicate sociolinguistic influences such as borrowing or analogical formations. The findings demonstrate that even between languages from different Austronesian subgroups, systematic phonemic alignments can emerge through sustained interaction. This research affirms the continued relevance of the comparative historical method in tracing sound change and typological convergence in multilingual societies. Furthermore, it contributes to the documentation and comparative understanding of regional linguistic variation in Indonesia, particularly within underexplored varieties like Deli Malay. The study encourages further comparative investigations involving morphosyntactic structures and broader Austronesian varieties to deepen the understanding of contact induced change and historical relationships in the archipelago.